(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2002)
The plant of St. John worth Hypericum perforatum L. was introduced into the isolated culture. The nutrient media both for callus tissue growth and for induction of processes of morphogenesis, plant growth and clonal micro- propagation were elaborated. Dynamics of the accumulation of raw and dry matters in callus tissue during cultivation as well as the cytological characteristic of callus tissue were studied. The cell and nudeus dimensions were defined.